Synthesis of rough-surface carriers for dry powder inhalation - Zhang, Fengying (2016)
For dry powder inhalation (DPI), aerosolization performance depends on particle properties such as material, surface roughness, size, shape, et al. In this work, the relation of the carrier material and drug delivery performance, surface roughness and drug delivery performance, as well as carrier stability were investigated. Mannitol and mannitol-lactose mixtures were studied initially as carrier materials. Mannitol/NaCl and mannitol/lactose microparticles that have similar size, shape, crystallinity and surface roughness were prepared successfully. The fine particle fractions (FPFs, a main parameter for the characterization of the particle aerosolization and deposition properties) of these two kinds of microparticles were studied. Mannitol was found to have lower interparticle force and better drug detachment, which resulted in a higher aerosolization performance than that of mannitol-lactose mixture. Based on the carrier material study, mannitol was selected and the relation between carrier surface roughness and aerosolization performance was studied. Four formulations of Mannitol/LB Agar (commercial) microparticles and a formulation of mannitol/NaCl microparticles that have similar size, shape, crystallinity but different surface roughness were prepared successfully. The relation between fine particle fraction (FPF) and drug adhesion mechanism was revealed. The results indicate high surface roughness provides a balance between low drug-carrier contact area and interlocking force. It offers a good drug adhesion and detachment yielding a high FPF. An FPF of 28.6±2.4% was achieved by microparticles transformed from spray-dried microparticles using 2% mannitol(w/v)/LB Agar as feed solution. It is comparable to the highest FPF reported in the literature using lactose and spray-dried mannitol as carriers. The results show that mannitol/LB Agar (commercial) microparticles have a short shelf-life of 3 months. Thus, the use of stabilizer for mannitol/LB Agar microparticles was investigated. The results indicate the composition of LB agar has a large influence on the stability of mannitol/LB Agar microparticles. An increase in the percentage of agar in LB Agar improved the stability of mannitol/LB Agar microparticles. Mannitol/LB Agar microparticles with an agar percentage composition of 7.26% were able to maintain the rough-surface and spherical shape for 21 months. With the introduction of a stabilizer, it is important to be able to control the surface morphology of the microparticles. As a result, the effect of LB Agar composition (percentage of agar in LB Agar) on particle morphology was studied. The results show that different percentage of agar in LB Agar offers pollen shape as well as rough spherical shapes with surfaces covered by crevices and rods. Pollen-shape 2%mannitol/LB Agar (lab-made) microparticles with needle-like rods prepared using LB agar with an agar percentage of 77-89% have a FPF of 32.7%±2.0%. Which is the highest drug delivery performance reported in literatures using mannitol and lactose as carrier particles.